Bilangan Peroksida pada Minyak Goreng Penjual Gorengan di Jalan Rajawali Kota Palangka Raya - Suratno Suratno; Ronny Victor Utomo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
A high peroxide value of used vegetable oil can lead to poisoning in the body and various diseases such as diarrhea, fat deposition in blood vessels, cancer and decrease of digestibility of fat and destruction of vitamin E. This study aims to determine the peroxide values in reused cooking oil on fried snack seller on Jalan Rajawali, Palangka Raya. A quantitative descriptive research design was used in this study. Random sampling technique was used to collect the sample — determination of peroxide value using iodometry method. Results show that based on quality requirements, from 14 cooking oil samples there were 78.6% of the samples comply with the peroxide value requirements and 21.4% of the samples did not comply with the peroxide value requirements. Samples which did not adhere to the peroxide value requirements are cooking oil that has been used for more than five repetitions.